Nephrotoxicity of cancer treatment in children. Issue 5 (October 2010) - Skinner, Roderick
Chronic renal impairment in children with cancer may be caused by the malignant process itself or result from adverse effects of treatment including cytotoxic drugs, radiotherapy, surgery or supportive treatment. Although severe renal chronic disease is uncommon, occurring in only 0.8% of long-term survivors of childhood cancer, 1.9% of all cases of established renal failure are due to malignancy and 0.8% to drug nephrotoxicity. The relative risk of severe renal chronic disease (compared with siblings) is 8.1, and that of renal failure or the need for dialysis is 8.9. The cytotoxic drugs most likely to cause important chronic nephrotoxicity are ifosfamide and cisplatin, both of which are used widely in many solid tumors and may cause chronic glomerular and/or renal tubular toxicity in 30–60% of treated children. Significant renal toxicity is less frequent with other chemotherapeutic drugs, but may result from treatment with carboplatin, methotrexate and nitrosoureas. Other cytotoxic drugs occasionally cause specific patterns of glomerular or tubular toxicity in children. Partial or unilateral nephrectomy leads to hypertrophy and hyperfiltration of the remaining renal tissue, and may result in microalbuminuria, hypertension and in rare cases, chronic renal impairment. Radiotherapy to a field including renal tissue may cause late onset chronic renal damage, manifest by hematuria, proteinuria, hypertension and anemia, sometimes progressing to chronic renal failure. Chronic nephrotoxicity is also common in survivors of hemopoietic stem cell transplantation, and is often multifactorial with contributions from prior chemotherapy, total body irradiation, immunosuppressive drugs and transplant complications, such as infection or hemorrhage. Patients at risk of renal damage should be monitored regularly with a defined surveillance protocol to enable timely management. General measures often employed to prevent or reduce nephrotoxicity include the use of intravenous hydration during drug administration and avoidance of known risk factors, such as high drug doses. Although numerous potentially nephroprotective drugs have been suggested and investigated, none have yet been introduced into clinical use in children due to the lack of proven efficacy. Improved understanding of the pathogenesis of nephrotoxicity is necessary to reduce the frequency and severity of this potentially serious complication of treatment in children with cancer.